Markers of Oral Lichen Planus Malignant Transformation. (26th February 2018) - Tampa, Mircea; Caruntu, Constantin; Mitran, Madalina; Mitran, Cristina; Sarbu, Isabela; Rusu, Laura-Cristina; Matei, Clara; Constantin, Carolina; Neagu, Monica; Georgescu, Simona-Roxana
Abstract : Oral lichen planus (OLP) is a chronic inflammatory disease of unknown etiology with significant impact on patients' quality of life. Malignant transformation into oral squamous cell carcinoma (OSCC) is considered as one of the most serious complications of the disease; nevertheless, controversy still persists. Various factors seem to be involved in the progression of malignant transformation; however, the mechanism of this process is not fully understood yet. Molecular alterations detected in OLP samples might represent useful biomarkers for predicting and monitoring the malignant progression. In this review, we discuss various studies which highlight different molecules as ominous predictors of OLP malignant transformation.